Ultra-low-Light CMOS Biosensor Complements Microfluidics to Achieve Portable Diagnostics. (2017) - Ding, Zhimin; Xu, Cai; Wang, Yifang; Pellegrini, Gianfranco
Abstract: Innovations in ultra low-light CMOS bio-optical sensor design, combined with microfluidics technology can enable a new generation of low cost, portable molecular diagnostics platforms. This combination of technologies have been applied successfully in a miniaturized qPCR system, and a chemiluminescence microfluidic immunoassay platform to detect a variety of infectious pathogens. Cost reduction and miniaturization of molecular test enabled by this technology will have positive impact on global battle against infectious diseases.